”Et nää on näitä meiän kyberhyökkäyksiä nämä” – The government of one and all in everyday digital security in Finnish Lapland - Salminen, Mirva (fi=Lapin yliopisto|en=University of Lapland|, 2022)
The government of one and all in everyday digital security in Finnish Lapland This study contextualises the gradual institutionalising of conventional concepts of cybersecurity by providing a more human-centric perspective. While discussion of cybersecurity can be encountered in daily news and in the workplace ever more frequently, its content and practical implications often remain abstract to everyday life. When cybersecurity is understandably addressed in highly technical and/or strategic terms, involving specific threat imageries and vocabularies, the mundane effects of the (un)successful securitisation of cyberspace can receive less attention. However, it is precisely these everyday effects that justify and undermine everyday cyber/digital security, and influence the respective security roles assigned to all citizens in emerging cyber-physical societies. Drawing out commonalities and differences between human security and governmentality studies, this thesis critically examines the entanglement of digitalisation and cyber/digital security in Finnish Lapland: opportunities it provides and concerns it awakes in sparsely populated areas characterised by harsh climate, cultural diversity, long distances, and infrastructural issues, all of which relate to imagery of the Arctic as a developing region. It investigates the power relations and positions thus created, mainly through securitisation, development, and resilience. However, it also incorporates the related techniques of responsibilisation, human rights, commercialisation, surveillance and transparency, and, finally, techniques of the self, which aim at the assimilation of modern governmentality but also provide the means for its resistance. While digitalisation in Lapland is carried out with the stated aim of continuing service provision or improving it, it is efficiency and cost calculations that drive it. Digitalisation and cyber/digital security are not generally examined together but as two separate trajectories. This thesis brings them together hence ...